1971
DOI: 10.3758/bf03335892
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of interpersonal attraction: Compliance with requests from liked and disliked others

Abstract: Sixty undergraduate females participated in an experiment designed to investigate the hypothesis that Ss would be more willing to comply with various requests from liked than from disliked others. Attraction was manipulated by varying both the apparent degree of attitude similarity between Ss and the requester and the favorability of ratings about the Ss ostensibly made by this individual. Results indicated that significantly more Ss complied with the requests of a liked than with those of a disliked other, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Both studies demonstrated that positive sentiment toward a target person increased the subject's willingness to help and that negative sentiment toward a target person decreased the subject's willingness to help. These results are consistent with the findings of Kelly and Byrne's (1976) study of helping behavior and compatible with the findings of Baron's (1971) and Regan's (1971) studies of compliance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Both studies demonstrated that positive sentiment toward a target person increased the subject's willingness to help and that negative sentiment toward a target person decreased the subject's willingness to help. These results are consistent with the findings of Kelly and Byrne's (1976) study of helping behavior and compatible with the findings of Baron's (1971) and Regan's (1971) studies of compliance.…”
Section: Discussionsupporting
confidence: 93%
“…Although many experiments have investigated possible determinants of interpersonal sentiment, such as liking (Berscheid, 1985;Heider, 1958), relatively little attention has been focused on the influence of interpersonal sentiment on various forms of social behavior (Baron, 1971;Saito, 1990). Baron (197 1) investigated the hypothesis that subjects would be more willing to comply with various requests from liked others than from disliked others.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence exists that we are particularly helpful to people we like Baron (1971). Therefore it is to a negotiator's benefit to attempt induce a positive mood or communicate in a positive tone to the other party.…”
Section: Agreeable and Negative Languagementioning
confidence: 94%
“…Rather, it appears the physically attractive, possibly because of all the favorable traits associated with them, are liked more than their less attractive counterparts (Horai, Naccari, & Fatoullah, 1974;Joseph, 1982;Snyder & Rothbart, 1971). And studies that have manipulated liking for the communicator have shown that increased liking for a communicator enhances the communicator's persuasiveness (Baron, 1971;Chaiken, 1980;Chaiken & Eagly, 1983;Regan, 1971).…”
Section: Physical Attractiveness Effectsmentioning
confidence: 99%